ANALISIS PENYEBAB SISA PIPA PRODUKSI KAPAL X MENGGUNAKAN NEW SEVEN TOOLS DAN FMEA (STUDI KASUS PADA PT. KRS) - Pratama, Aditya Tri; Nugraha, Isna (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
PT. KRS is a company operating in the maritime sector, especially ship production. Apart from producing ships, this company also has the capability to repair and overhaul. In 2023 PT. KRS launched ship However, in making this ship there is still a lot of material remaining. This research is devoted to pipe materials. This research aims to minimize the amount of remaining pipe material from the production of ship X. To overcome this problem, we need to find out what variables influence the amount of remaining pipe material. This research uses New Seven Tools analysis and the Failure Mode and Effect Analysis (FMEA) technique. After processing and analysis, the elements determined to be the cause of the large amount of remaining pipe material were the lack of ability and accuracy of workers in the management and maintenance of materials and machines. Apart from that, the environment also influences the quality of the material. Therefore, assessing potential improvements includes training and socializing Standard Operating Procedures (SOP) for machine operation, carrying out routine maintenance, and maintaining the project material storage warehouse.